Effects of Working Capital Management on Profitability: Evidence from the Topfive Beer Brewery Firms in the World - Uchenna, Ani Wilson; Mary, Okwo Ifeoma; Okelue, Ugwunta David (Asian Economic and Financial Review, 2012)
The impact of working capital management on the profitability of manufacturing firms has attracted the attention of researchers in different countries of the world in recent times. This research expands the horizon of knowledge in this area by shedding more light on working capital management as measured by the cash conversion cycle (CCC), and how the individual components of the CCC influence the profitability of world leading beer brewery firms. Multiple regression equations were applied to a cross sectional time series data of five world leading beer brewery firms after ensuring that the data are stationary and co-integrated. The outcome of the analysis clearly pinpoint that working capital management as represented by the cash conversion cycle, sales growth and lesser debtors’ collection period impacts on beer brewery firms’ profitability.